Deletion of Wild-type p53 Facilitates Bone Metastatic Function by Blocking the AIP4 Mediated Ligand-Induced Degradation of CXCR4 - Li, Qiji; Wang, Min; Zeng, Leli; Guo, Wei; Xu, Yuandong; Li, Chenxin; Lai, Yingrong; Ye, Liping; Peng, Xinsheng (Frontiers in Pharmacology, 2022)
Background: Management of patients with prostate cancer and bone metastatic disease remains a major clinical challenge. Loss or mutation of p53 has been identified to be involved in the tumor progression and metastasis. Nevertheless, direct evidence of a specific role for wild-type p53 (wt-p53) in bone metastasis and the mechanism by which this function is mediated in prostate cancer remain obscure. Methods: The expression and protein levels of wt-53, AIP4, and CXCR4 in prostate cancer cells and clinical specimens were assessed by real-time PCR, immunohistochemistry and western blot analysis. The role of wt-p53 in suppressing aggressive and metastatic tumor phenotypes was assessed using in vitro transwell chemotaxis, wound healing, and competitive colocalization assays. Furthermore, whether p53 deletion facilitates prostate cancer bone-metastatic capacity was explored using an in vivo bone-metastatic model. The mechanistic model of wt-p53 in regulating gene expression was further explored by a luciferase reporter assay and chromatin immunoprecipitation (ChIP) assay. Results: Our findings revealed that wt-p53 suppressed the prostate cancer cell migration rate, chemotaxis and attachment toward the osteoblasts in vitro. The bone-metastatic model showed that deletion of wt-p53 remarkably increased prostate cancer bone-metastatic capacity in vivo. Mechanistically, wt-p53 could induce the ligand-induced degradation of the chemokine receptor CXCR4 by transcriptionally upregulating the expression of ubiquitin ligase AIP4. Treatment with the CXCR4 inhibitor AMD3100 or transduction of the AIP4 plasmid abrogated the pro-bone metastasis effects of TP53 deletion. Conclusion: Wt-p53 suppresses the metastasis of prostate cancer cells to bones by regulating the CXCR4/CXCL12 activity in the tumor cells/bone marrow microenvironment interactions. Our findings suggest that targeting the wt-p53/AIP4/CXCR4 axis might be a promising therapeutic strategy to manage prostate cancer bone metastasis.